Inflammatory diseases of the pelvic organs in women as the leading factor of formation of tubal-peritoneal infertility - Avramenko, N. V. (Zaporozhye Medical Journal, 2014)
Introduction Patients with inflammatory diseases of the sexual sphere reach 60-65% of all gynecologic patients. Inflammatory diseases of the pelvic organs are some of the causes of non-hormonal infertility, ectopic pregnancy, miscarriage, diseases and malformations of the fetus, surgical interventions. Results of multicenter studies showed that only 25% of couples who were diagnosed tubal-peritoneal infertility, noted no sexually transmitted infections in the history. Research objective On the basis of data analysis of the specialized literature to summarize and present the modern view on etiology, modern inflammatory diseases of the small pelvis, modern treatment strategy aimed at preservation of anatomical and functional condition of the fallopian tubes and ovaries. Materials and methods Unfortunately, in our country there is no real data on the number of women suffering from inflammatory diseases of the pelvic organs. Factors that affect the difficulty of it identification were marked: - non-recognition of the disease by patients; - difficulty in gaining access to medical care; - subjective method of diagnostics of diseases; - lack of diagnostics and laboratory facilities in many regions; - lack of funds and necessary medicines in the health system. Etiological factor is often microbial Association, which can be presented as absolute pathogens with a predominantly sexual way of transmission and endogenous anaerobic and aerobic. Mainly Neisseria gonorrheae (25-50%) and Chlamydia trachomatis (25-30%), Peptococcus, Peрtostreptococcus, Bacteroides, Gardnerella vaginalis, Haemophilus influenzae and other gram-negative bacteria, Streptococcus agalactiae, Mycoplasma hominis, Mycoplasma henitalium, Ureaplasma urealyticum. Some role has bacterial-viral combination of mycoplasmic, ureoplasmic infection with herpes simplex virus types 1 and 2, cytomegalovirus, Epstein-Barr and human papilloma virus. The primary lesion of the fallopian tubes and ovarian tissue determines violations of reproductive function. Chronic inflammatory diseases of female genital organs cause formation of adhesions in the pelvis with involvement of the reproductive organs, leading to infertility, chronic pelvic pain. Conclusions Acute oophoritis treatment subordinated to the General principles of treatment of infectious pathology and involves the provision of adequate antibacterial therapy, which in most cases is empirical and assumes the risk of inflammatory diseases of the pelvic organs. It is recommended to assess the first results of treatment in 72 hours after the start of treatment. This is especially important in severe and moderate forms of the disease. The success of the chosen tactics can be judged by the improvement in clinical symptoms. Special attention should be paid to the prevention and recommendations on healthy way of life. Rehabilitation of women’s reproductive function should be done on all stages of rendering medical assistance, especially at the outpatient stage. "Ultimately, the responsibility for treatment always lies on the doctor" - this phrase over European guidelines for the treatment of PID. We fully subscribe to this conclusion.